Bilgi selinin agnostik kıyıları: badioucu öznenin hakikat krizi. - Kahvecioğlu, Anıl (Felsefelogos, 2023)
This article explores the potential impact of skeptical and agnostic ethics on the subject-truth relationship within the context of Badiou’s philosophy. Examining the capacity of technology to create knowledge abundance and its influence on the feeling of doubt, this article asks the following questions within a Badiouian framework: How can a skeptical individual, situated amidst the flood of knowledge today, make a decision about whether an event is an event? In a world where fidelity to a truth is surrounded by constant doubt, how is a fidelity practice towards truth possible? How can a potential subject establish a connection with a concealed truth within a world that has been oneified? Within the logic of a world where knowledge conceals the possibility of truth like never before, how can a subject create a hole within this logic? In light of these questions and as a response to them, this article questions the possibility of a pre-subjective position that upholds the Idea of Truths.